Main active components of Jiawei Gegen Qinlian decoction protects against ulcerative colitis under different dietary environments in a gut microbiota-dependent manner. (August 2021) - Li, Qinmei; Cui, Yao; Xu, Baichang; Wang, Yuhan; Lv, Feifei; Li, Zheng; Li, Huan; Chen, Xiaogang; Peng, Xiaomin; Chen, Yating; Wu, Enyun; Qu, Dongshuai; et al.
Abstract: As an effective drug against acute enteritis diarrhea, Gegen Qinlian decoction (GQD) has a history of 2000 years. However, the potential molecular mechanism through which GQD could protect intestinal barrier from ulcerative colitis (UC) still remains undefined. As an important part of the homeostasis of the colon, gut microbiota is closely related to the dynamic evolution of the surrounding environment and the adjustment of dietary structure. At present, the effectiveness and mechanism of Jiawei Gegen Qinlian decoction against UC in different dietary environments are not clear. Here, the main active components of Jiawei Gegen Qinlian Decoction (PBM), were selected to construct a reasonable and effective compound scheme. We adopted "5% dextran sulfate sodium (DSS)" and "high temperature and humidity + high sugar and high fat + alcohol + 5%DSS" to induce UC rat models in general environment and UC rat models in Lingnan area, respectively. Then, we examined the therapeutic effects of PBM (89.96 mg/kg and 179.92 mg/kg) on two kinds of UC rats. The role of gut microbiota in the anti-UC effect of PBM was identified by intestinal flora consumption and fecal microbiota transplantation (FMT) experiments. Subsequently, we monitored the alterations of gut microbiota and fecal metabolism in the rat colon by 16Sr DNA technique and targeted metabonomics, respectively. The colon inflammation of the PBM-treated and the FMT-treated rats both showed significant relief, as evidenced by a reduction in body weight loss, bloody stool, diarrhea, disease activity index (DAI) score, shortening of colon length as well as decreased colon histology damage. Interestingly enough, the depletion of intestinal flora took away the protective effect of PBM, confirming the importance of intestinal flora in the anti-UC effect of PBM. Then our findings suggested that PBM could not only regulate the gut microbiota by increasing Akkermansia and Romboutsia but also decrease Escherichia-Shigella. More importantly, PBM could increase the production of propionate and total short-chain fatty acids (SCFAs) in colitis rats, regulate medium and long chain fatty acids (M-LCFAs), maintain bile acids (BAs) homeostasis, and regulate amino acids (AAs) metabolism. The transformation of intestinal environment might be related to the upregulation of anti-inflammation, anti-oxidation and tight junction protein expression in colonic mucosa. In summary, PBM showed potential for anti-UC activity through gut microbiota dependence and was expected to be a complementary and alternative medicine herb therapy. Graphical Abstract: ga1